Acute Kidney Injury in Non-critically Ill Children and Correlation With Cystatin C in the Diagnosis of Acute Kidney Injury: A Single Centre Prospective Cohort Study: Cystatin C in Acute Kidney Injury - Gupta, Gunjan; Sharma, Shobha; Kapoor, Kanika; Rani, Anita; Gera, Rani (Journal of Pediatric Nephrology, 2023)
Background and Aim: Acute kidney injury (AKI) is an acute decline in function and inability to regulate acid, electrolyte, and fluid balance. AKI can be classified as community-acquired AKI (CA-AKI) and hospital-acquired AKI (HA-AKI) depending on the time of onset. Most studies have been conducted on critically ill populations, mainly considering the HA-AKI cases. Limited studies were conducted on CA-AKI, especially in non-critically ill children. Methods: A prospective cohort study in 505 non-critically ill hospitalized children (1 month to 12 years) after screening 750 children. Baseline creatinine was calculated using a computational method assuming a normal glomerular filtration rate (GFR) for age, hence all communities, as well as hospital-acquired AKI, were included. Kidney disease improving global outcome (KDIGO) criteria was used for classification and also serum cystatin -C levels were done to diagnose AKI. Results: Fifteen percent (15.64%) of children had AKI, of which 83.54% had CA-AKI and 16.46% had HA-AKI. Of all patients with AKI, 54.43% were exposed to nephrotoxic drugs and 53.49% (23) had received 2 or more nephrotoxic drugs, and 34.18% of patients had sepsis, 35.44% of patients had dehydration. Patients with HA-AKI had a significantly longer duration of stay (15.23±5.42 days) compared to CA-AKI patients (7.48±6.42 days) and were also exposed to nephrotoxic drugs. Cystatin C had a specificity of 88.50% and a negative predictive value of 93.80%. Conclusion: Non-critically ill hospitalized children are at significant risk for AKI and need more vigilant monitoring. CA-AKI should be detected proactively because they are often underreported. Cystatin-C has good specificity and negative predictive value for diagnosing AKI.